GLIMPSES OF SUFISM IN ENGLISH LITERATURE (International Journal of Food and Nutritional Sciences, 2022)
Sufism, the mystical dimension of Islam, has deeply influenced English literature through its spiritual concepts, poetic expressions, and philosophical ideas. Over the centuries, English literary figures have drawn inspiration from Sufi themes such as divine love, self-annihilation, and the soul's journey towards God. This study explores the subtle but significant presence of Sufism in English literature, tracing its influence from the works of poets like William Blake and Samuel Taylor Coleridge to contemporary authors. By analyzing key texts, the study highlights the ways in which Sufi philosophy has shaped themes of transcendence, mysticism, and universal love in English literature. This research further illustrates how Sufi principles have been adapted within the Western literary canon to reflect deeper spiritual truths and human connection to the divine.